Study of Pregabalin as Premedication for Anxiolysis in Patients Undergoing Elective Surgery - Chaudhary, Amit; Sharma Bhattarai, Amit; Joshi, Pankaj; Shrestha, Anil (Nepal Journal of Medical Sciences, 2025)
Introduction: Preoperative anxiety affects 25–80% of surgical patients, impairing postoperative recovery. Pregabalin, by modulating neuronal excitability, may alleviate this anxiety. This study evaluated the efficacy of pregabalin 150 mg in reducing preoperative anxiety. Methods: A prospective observational study included 50 ASA I/II patients scheduled for elective surgery under general anesthesia. Preoperative anxiety was assessed using the Beck Anxiety Inventory (BAI-Nepali), a 21-item self-report scale (scores 0–3 per item). Baseline BAI scores, heart rate, and blood pressure were recorded. Patients received oral pregabalin 150 mg as premedication, and BAI scores and hemodynamic parameters were reassessed after 120 minutes. Results: At baseline, 94% (n=47) had minimal anxiety (BAI: 2.22 ± 2.85), 4% (n=2) mild, and 2% (n=1) moderate. Post-intervention, all patients (100%) exhibited minimal anxiety (BAI: 1.4 ± 1.41, p=0.003). Hemodynamic parameters (heart rate, systolic/diastolic blood pressure, mean arterial pressure) remained stable. Conclusions: A single dose of pregabalin 150 mg significantly reduced preoperative anxiety in elective surgical patients, with no adverse hemodynamic effects. These findings support its use as an effective anxiolytic premedication.